Pengujian Aplikasi Keuangan Kaspro Dengan Metode Alpha Dan Beta Testing - Wijaya, Dedy; Sukma Ayu, Rini; Abdul Aziz, Farhan; Martua Sipahutar, Ruben; Luthfi Charis Naja, Zunan; Yusuf, Muhammad (CV. Shofanah Media Berkah, 2024)
The KasPro application is a digital-based financial application that is used to carry out online transactions. Users can carry out various kinds of transactions, including transfers, payments and other transactions. With this application, it is hoped that users can make transactions anywhere and anytime. However, some users experience bugs or errors, and there are several functions or features that need to be improvised. Therefore, testing is needed to provide suggestions and improvements to users. KasPro financial application testing is carried out using the Alpha and Beta methods. Alpha testing uses a Black box approach to ensure the application functionality meets user requirements based on the user interface. This Alpha Test covers key functions such as login, balance management, payment transactions, and transaction history. Alpha testing results show that 75% of test cases are successful. Beta testing involved 31 respondents aged between 18 and 45 years, who came from the general public and students. Feedback on performance, usability, and stability is collected through questionnaires. Beta testing results show user satisfaction of 72%. Overall, the KasPro application meets most of the technical needs and user expectations, although it still needs improvements in the interface and application performance. This research was conducted to ensure application functionality and user satisfaction, as well as provide suggestions for improvements to the developer.